Characteristics and Energy Potential of Bio-Briquettes from Cassava Peel, Water Hyacinth, and Sawdust - Salimah, Shofi Fitrotis; Akhmad, Sabarudin; Arendra, Anis (Jurnal Pendidikan dan Teknologi Indonesia, 2025)
Abstract. Agricultural waste biomass direct burning to generate heat in industrial applications is inefficient. In addition, the difficulty in shipping and storage is due to its large volume and non-uniform shape. One approach to overcome this problem is by compacting the biomass to increase density, improve calorific value, and save a better combustion rate. In this study, the screw extruder machine was designed to compress, heat, and extrude bio-briquettes to form a hollow hexagon cross-section with an inscribed circle diameter of 52mm from biomass waste. The water hyacinth and cassava peel biomass were each dried and chopped into small particles before being mixed with sawdust. Cassava peel flakes also act as a binder in this mixture. We investigated the effect of biomass composition and extruder heating temperature on the calorific heating value and burning rate of bio-briquettes. We complete the experiments at three temperature levels and three levels of biomass composition. The results of the study found that there was no significant effect of the heating temperature factor on the calorific value and the rate of combustion of briquettes. While the composition of biomass impact significantly on the calorific value and burning rate of bio-briquettes. The calorific value reached 19.16 MJ/kg in the 50% sawdust, 30% water hyacinth, and 20% cassava peel bio-briquettes composition with a burning rate of 1.49 g/min. Water hyacinth and cassava peel waste recovery as an energy source not only turns waste into valuable resources but again becomes a solution to the problem of water hyacinth pest invasion and even provides economic and ecological benefits.